In Vitro Study of the Combination of Doxorubicin, Curcuma xanthorrhiza, Brucea javanica, and Ficus septica as a Potential Novel Therapy for Metastatic Breast Cancer - Sutejo, Ika Rahmawati; Putri, Herwandhani; Handayani, Sri; Jenie, Riris Istighfari; Meiyanto, Edy (Indonesian Journal of Pharmacy, 2019)
Less optimized therapeutic effects constrain the use of doxorubicin as the main agent of chemotherapy for metastatic breast cancer, resistance and side effects. Therefore we need a combination of more than one chemopreventive agent which has different molecular targets to solve that problem. The aims of this study is to prove the inhibitory effect of ethanolic extract of rhizome of Curcuma xanthorrhiza (ECx), fruit of Brucea javanica (EBj), leave of Ficus septica (EFs) and doxorubicin (Dox) alone and its combination on migration and invasion of a highly metastatic 4T1 breast cancer cell line. Cytotoxic activity of single and combination treatment was evaluated by MTT assay, followed by an experiment of apoptosis induction by using flow cytometry. The inhibitory effect on migration was observed by the scratch wound-healing assay. Furthermore, the observation of the activity of matrix metalloproteinase-9 (MMP-9) was analyzed by gelatin zymography. The results showed that ECx, EBj, EFs, and Dox has cytotoxic activity on 4T1 cells with the value of IC50 respectively 49.7±1.53mg/mL, 59.9±1.79mg/mL, 15.2±2.12mg/mL and 1.2±0.23mM. Furthermore, combination of ECx-EBj-Dox and ECx-EBj-EFs revealed synergistic effect on 4T1 cells and decrease cell viability through the induction of apoptosis and necrosis. Based on wound healing assay, 24 hours incubation of this combination inhibited 4T1 cells migration compared to single treatment. Gelatin zymography analysis showed that this combination also inhibited the activity of MMP-9 greater than a single use. Curcuma xanthorrhiza, Brucea javanica, and Ficus septica may have potential to be developed as a combination with or without doxorubicin for metastatic breast cancer treatment.